The Lasting Legacy of the Sarakuna: A Narrative Exploration of Their Significant Roles in the Aftermath of the Sokoto Caliphate Jihad and Beyond (2025) - Bashar, Tambari Abbas (Darul Yasin Al Sys, 2025)
This study examines the roles of Sarakuna in the remnants of the Sokoto Caliphate, focusing on their contributions to Da'awah, industry, economic activities, professional services, security, mosques, schools, health, development projects, marital affairs, and Sharia delivery. The study reveals that Sarakuna play pivotal roles in maintaining peace, security, and tranquility in their domains, and their influence extends to various aspects of life, including education, healthcare, and economic development.